If possible, solve the system of equations. Use any method. If there is not a unique solution to the system, state a reason. \[ \begin{array}{ll}4 x-y=22 & \text { (1) } \\ 7 x+3 y=48 & \text { (2) }\end{array} \]
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve the system of equations, we'll use the substitution or elimination method. Let's use substitution for this example. From equation (1): \[ 4x - y = 22 \] We can rearrange it to express \( y \) in terms of \( x \): \[ y = 4x - 22 \] Now, substitute \( y \) into equation (2): \[ 7x + 3(4x - 22) = 48 \] Expand and simplify: \[ 7x + 12x - 66 = 48 \] Combine like terms: \[ 19x - 66 = 48 \] Now, isolate \( x \): \[ 19x = 48 + 66 \] \[ 19x = 114 \] \[ x = \frac{114}{19} \] \[ x = 6 \] Now, substitute \( x = 6 \) back into the equation for \( y \): \[ y = 4(6) - 22 \] \[ y = 24 - 22 \] \[ y = 2 \] Thus, the solution to the system of equations is \( x = 6 \) and \( y = 2 \). To verify, we can plug these values back into the original equations: For (1): \[ 4(6) - 2 = 22 \] \[ 24 - 2 = 22 \] (True) For (2): \[ 7(6) + 3(2) = 48 \] \[ 42 + 6 = 48 \] (True) The solution checks out! Therefore, the unique solution to the system is \( (x, y) = (6, 2) \).